{2×[14+(5+x)÷6]-5}÷9+7=10
MariaOanaK130:
Răspunsul corect este 7
Răspunsuri la întrebare
Răspuns de
2
{2×[14+(5+x):6]-5}:9=10-7
{2×[14+(5+x):6]-5}:9=3
{2×[14+(5+x):6]-5}=3×9
2×[14+(5+x):6]-5=27
2×[14+(5+x):6]=27+5
2×[14+(5+x):6]=32
14+(5+x):6=32:2
14+(5+x):6=16
(5+x):6=16-14
(5+x):6=2
5+x=2×6
5+x=12
x=12-5
x=7
{2×[14+(5+x):6]-5}:9=3
{2×[14+(5+x):6]-5}=3×9
2×[14+(5+x):6]-5=27
2×[14+(5+x):6]=27+5
2×[14+(5+x):6]=32
14+(5+x):6=32:2
14+(5+x):6=16
(5+x):6=16-14
(5+x):6=2
5+x=2×6
5+x=12
x=12-5
x=7
Răspuns de
3
{2×[14+(5+x)÷6]-5}÷9+7=10
{2×[14+(5+x)÷6]-5}÷9=10-7
{2×[14+(5+x)÷6]-5}÷9=3
2×[14+(5+x)÷6]-5=9×3
2×[14+(5+x)÷6]-5=27
2×[14+(5+x)÷6]=27+5
2×[14+(5+x)÷6]=32
14+(5+x)÷6=32:2
14+(5+x)÷6=16
(5+x)÷6=16-14
(5+x)÷6=2
5+X=6×2
5+X=12
X=12-5
X=7
{2×[14+(5+x)÷6]-5}÷9=10-7
{2×[14+(5+x)÷6]-5}÷9=3
2×[14+(5+x)÷6]-5=9×3
2×[14+(5+x)÷6]-5=27
2×[14+(5+x)÷6]=27+5
2×[14+(5+x)÷6]=32
14+(5+x)÷6=32:2
14+(5+x)÷6=16
(5+x)÷6=16-14
(5+x)÷6=2
5+X=6×2
5+X=12
X=12-5
X=7
Alte întrebări interesante
Matematică,
8 ani în urmă
Limba română,
9 ani în urmă
Matematică,
9 ani în urmă
Matematică,
9 ani în urmă
Limba română,
9 ani în urmă